2012
DOI: 10.1002/cne.23104
|View full text |Cite
|
Sign up to set email alerts
|

Biciliated ependymal cell proliferation contributes to spinal cord growth

Abstract: Two neurogenic regions have been described in the adult brain, the lateral ventricle subventricular zone and the dentate gyrus subgranular zone. It has been suggested that neural stem cells also line the central canal of the adult spinal cord. Using transmission and scanning electron microscopy and immunostaining, we describe here the organization and cell types of the central canal epithelium in adult mice. The identity of dividing cells was determined by three-dimensional ultrastructural reconstructions of [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
133
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(156 citation statements)
references
References 77 publications
21
133
0
1
Order By: Relevance
“…β-catenin: The β-catenin antibody used in this study detects a band of 92 kDA in lysates of HeLa cells and the protein localizes to cell boundaries (manufacturer's website). Consistent staining patterns with other bcatenin antibodies in spinal cord was also reported (Alfaro-Cervello et al, 2012). MAGI2 : The MAGI2 antibody used in this study recognizes a bands of 180, 160 and 105 kDA and does not cross react with related molecules.…”
Section: Methodssupporting
confidence: 86%
“…β-catenin: The β-catenin antibody used in this study detects a band of 92 kDA in lysates of HeLa cells and the protein localizes to cell boundaries (manufacturer's website). Consistent staining patterns with other bcatenin antibodies in spinal cord was also reported (Alfaro-Cervello et al, 2012). MAGI2 : The MAGI2 antibody used in this study recognizes a bands of 180, 160 and 105 kDA and does not cross react with related molecules.…”
Section: Methodssupporting
confidence: 86%
“…For example, Meletis and associates 5 identified three distinct ependymal cell populations in the mouse central canal 1 based on morphological differences, but was unable to determine any molecular marker delineating these subpopulations. AlfaroCervello and associates 22 described biciliated ependymal cells of the central canal that are nestin positive and glial fibrillary acid protein (GFAP) negative, and which proliferate slowly under normal growth conditions. Dromard and associates 17 indicated a cluster of nestin-positive cells located in the ventral subependymal region as being a possible neurogenic niche, whereas Hamilton and associates 8 reported that cells with stem cell characteristics may be located in the dorsal pole of the central canal and have a tanycytelike morphology.…”
Section: Introductionmentioning
confidence: 99%
“…3,28,30,38 In vitro, cells from the SEL of both mice and humans can also assume stem cell properties, generating multipotent neurospheres in culture. 1,7,28 Given these findings, experimental treatments that exploit the SEL as a source of endogenous neural stem cells are currently being explored in rodent models of SCI, with some success. 32 However, as with other promising treatments for SCI, translation from rodent models to human patients will present a challenging next step.…”
mentioning
confidence: 99%